Effect of Different Mechanical Properties of Core Build-up Materials on the Root Furcation of A Severely damaged Primary Molar: A Finite Element Analysis - Suwannasri, Nuttha; Thaungwilai, Kunyawan; Singhatanadgid, Pairod; Chaianant, Nichamon; Singhatanadgit, Weerachai; Pultanasarn, Piyaporn (Srinakharinwirot University Dental Journal (E-ISSN 2774-0811), 2023)
Objectives: To assess the von Mises stress and stress distribution pattern on the root furcation of a severely damaged primary molar restored with different core build-up materials and stainlesssteel crown (SSC). Materials and Methods: The finite element analysis was used to investigate stresses induced in the tooth structures included a sound primary molar and severely damaged primary molars restored with four different core-build up materials, including flowable composite core build-up, bulkfill resin composite, RMGIC and nano-RMGIC. The maximum von Mises stress was used to represent the internal load induced in the model. Results: Overall maximum von Mises stresses was the highest in the sound tooth. However, when focusing on apico-cervical aspect, all restored primary molars showed higher maximum von Mises stress than the sound tooth. The stress distribution pattern of each group was similar, except for the nano-RMGIC group that showed high stress concentrated at the tooth furcation and the buccal aspect of the root furcation. From the ratio of its tensile strength and the maximum von Mises stress, the nano-RMGIC possessed the highest fracture resistance, followed by bulk-fill composite, RMGIC and flowable composite core group, respectively. Discussion: Although nano-RMGIC possessed the highest fracture resistance, it showed an unfavorable stress distribution pattern, which caused high stress at the root furcation. The bulk-fill composite possessed not only high fracture resistance but also favorable stress distribution. Conclusion: The present study introduces crucial information that could lead to an alternative treatment for severely damaged primary molar. Our findings recommend bulk-fill composite as a potential core build-up material. > ว.ทันต.มศว ปีที่ 16 ฉบับที่ 1 พ.ศ. 2566 หน้า 62-77. > SWU Dent J. 2023;16(1): 62-77.